The problem of tonsillectomy and adenoidectomy in the allergic person - Özkaragöz, Kemal; Dereli, Ataman (The Turkish Journal of Pediatrics, 1965)
A study was made in the Allergy Department of Hacettepe Medical Center of types of allergic disorders and the causes and results of tonsillectomy and adenoidectomy in 39 patients with tonsillectomies out of 230 allergic patients with respiratory tract allergy who were under hyposensitization. The majority were operated on for recurrent tonsillitis, rhinitis and bronchial asthma. The results of this operation among allergic patients were poor. Only five patients had complete or partial recovery, the others remained either unchanged or became worse. None of the patients among the unoperated group, showed any exacerbation of allergic symptoms clinically during the period of observation. Indications for tonsillectomy had been accepted as similar in allergic and nonallergic children. However allergy per se cannot be considered a mandate for tonsillectomy but should be an index warning of the incipient danger in performing a tonsillectomy. We believe that there are very few cases among allergic persons in which tonsillectomies are necessary. Our experience as well as that of many other authors showed that poor results from the operation often indicate that these patients may have been allergic and that common allergic symptoms such as sneezing, rhinorrhea, nasal blockage, bronchitis and asthma should not necessarily be considered indications for tonsillectomy. In order to avoid negative results following tonsillectomy, all candidates for this operation should have a thorough study of their personal and family allergic history and whenever allergic and infectious conditions coexist, the decision for surgery should be made only after a trial period of allergic management. If after such a period, the allergy improves, but the infectious state remains, tonsillectomy may be considered. The operation should be performed in a pollenfree season and allergic management should be continued postoperatively.